Targeting the cell cycle in breast cancer: towards the next phase - Thu, KL; Soria-Bretones, I; Mak, TW; Cescon, DW (Cell cycle (Georgetown, Tex.), 2018)
Deregulation of the cell cycle is a hallmark of cancer that enables limitless cell division. To support this malignant phenotype, cells acquire molecular alterations that abrogate or bypass control mechanisms in signaling pathways and cellular checkpoints that normally function to prevent genomic instability and uncontrolled cell proliferation. Consequently, therapeutic targeting of the cell cycle has long been viewed as a promising anti-cancer strategy. Until recently, attempts to target the cell cycle for cancer therapy using selective inhibitors have proven unsuccessful due to intolerable toxicities and a lack of target specificity. However, improvements in our understanding of malignant cell-specific vulnerabilities has revealed a therapeutic window for preferential targeting of the cell cycle in cancer cells, and has led to the development of agents now in the clinic. In this review, we discuss the latest generation of cell cycle targeting anti-cancer agents for breast cancer, including approved CDK4/6 inhibitors, and investigational TTK and PLK4 inhibitors that are currently in clinical trials. In recognition of the emerging population of ER+ breast cancers with acquired resistance to CDK4/6 inhibitors we suggest new therapeutic avenues to treat these patients. We also offer our perspective on the direction of future research to address the problem of drug resistance, and discuss the mechanistic insights required for the successful implementation of these strategies.